Analysis of the Attractiveness and Sustainability of Surfing Tourism in the Mentawai Islands - Latifah Awaliya (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2024)
This study aims to analyze the attractiveness and sustainability of surfing tourism in the Mentawai Islands. The research background focuses on the rapid growth of surfing tourism, which presents challenges in maintaining a balance between tourist appeal and environmental and social sustainability. This research employs a qualitative approach with a case study method, where data were collected through direct observation of surfing conditions and literature review. The analysis utilizes the Tourism Area Life Cycle (TALC) model to identify the development phases of surfing tourism and its impact on attractiveness and sustainability. The results show that the attractiveness of surfing tourism in the Mentawai Islands is influenced by natural beauty, supporting facilities, accessibility, and unique local culture. The consistent and high-quality waves at several spots, such as Macaronis, Hollow Trees, and Playgrounds, are the main attractions for surfers. However, the study also identifies significant challenges to sustainability due to environmental degradation and economic dependency on the tourism sector. According to the TALC analysis, the Mentawai Islands are currently in the development phase, requiring holistic and sustainable management to prevent a future decline in attractiveness.